Beacon Hill The Life and Times of a Neighborhood - Li-Marcus, Moying, 1954-; Klee, Jeffrey E.; Project Muse.; Project Muse. (2019)
An insightful study of urban transformation recalls four centuries in the life of Boston's most famous neighborhood, tracing social, economic, and political changes in the community. Originally published by Northeastern University Press in 2002. With a new foreword by Jeffrey E. Klee.
A New Vision for an Old Hill, 1630-1900 -- The Shawmut Peninsula -- When Patriots Gathered -- The Mount Vernon Proprietors -- Moving Mountains--Literally -- Enclave of Charm: Louisburg Square -- "Brahmins" on the South Slope -- Sliding Fortunes -- The North Slope -- America's First Black Church -- The Fight against Slavery -- Beacon Hill Bohemian -- The Beacon Hill Renaissance, 1900-1930 -- "Streetfighter": Marian Nichols -- Real Estate Savvy: The Codmans -- Architectural Passion: Frank A. Bourne -- Launching the Beacon Hill Association -- A Gentleman and a "Bull Dog": Arthur D. Hill -- Developers, Beware -- A Tale of Two Main Streets -- Enter the Automobile -- The "Lost Generation" -- Christmas on the Hill -- War & Peace, 1940-1950 -- Japanese and Other "Strangers" -- Return of the GI -- The Brick Savers Ride Again -- Mothers against Storrow Drive -- Nowhere to Go but Down -- West End Story -- A Hill for History -- Reinventing Beacon Hill, 1960-2000 -- Awakenings -- Battle for the North Slope -- Today's Interior, Yesterday's Wall -- Town and Gown -- The Summer of Love -- The '60s Generation Digs In -- Hill House -- Charles Street Fair -- Small Miracles -- Beacon Hill Village in the New Millennium.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No derivatives 4.0 International License
Reprint of 2002 edition with new foreword.
Includes bibliographical references (pages 153-165) and index.
Description based on print version record.
Keywords: Massachusetts -- Boston -- Beacon Hill; Massachusetts -- Boston; Boston (Mass.) -- History; Beacon Hill (Boston, Mass.) -- History; History; Electronic books; Electronic books